NOISE INDUCED STRESS - Manoj kumar (International Journal of Research Science and Management, 2016)
Noise has the potential to cause stress reaction. Chronic noise induced stress enhance the aging of the myocardium and thus increase the risk of myocardial infarction. The involved path mechanism include acute increase of catecholamines or cortisol under acute noise exposure and an interaction between endocrine reactions and intracellular Ca/Mg shifts. Chronic noise exposure of animals on a diet with suboptimal magnesium content led to increase of connective tissue and calcium, and decrease of magnesium in the myocardium. These changes were correlated to noradrenaline and normal aging. Post mortem studies of hearts from victims of ischemic heart diseases confirmed the importance of Ca/Mg shifts in humans. Recent epidemiological studies support the importance of noise as a risk factor in circulatory and heart diseases, especially in myocardial infarction.